2019
DOI: 10.1108/igdr-10-2018-0109
|View full text |Cite
|
Sign up to set email alerts
|

Capital flight and extent of corruption control in the least corrupt African countries

Abstract: PurposeThe purpose of this paper is to investigate the effect of corruption control on capital flight in the least corrupt African countries.Design/methodology/approachUsing panel data covering the period of 1996-2010.FindingsThe results show that the extent of corruption, the total natural resources rent are statistically significant and affect positively the capital across the pooled, random and fixed effects. Inflation and economic growth are also found to have a negative impact on capital flight. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For instance, the authors found a negative relationship between political governance and trade in Sub‐Saharan Africa. Evidence from Central African Republic also showed that the country's governance systems underline state fragility, promote capital flight, and negatively affect foreign direct investment and development (Yapatake Kossele, 2020; Yapatake Kossele & Ngaba Mbai‐Akem, 2019; Yapatake Kossele & Shan, 2018). Hence, striving for good governance is very critical for development in the continent.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…For instance, the authors found a negative relationship between political governance and trade in Sub‐Saharan Africa. Evidence from Central African Republic also showed that the country's governance systems underline state fragility, promote capital flight, and negatively affect foreign direct investment and development (Yapatake Kossele, 2020; Yapatake Kossele & Ngaba Mbai‐Akem, 2019; Yapatake Kossele & Shan, 2018). Hence, striving for good governance is very critical for development in the continent.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Scholarly investigations have revealed that acts of terrorism can exert an adverse impact on investor sentiment, subsequently precipitating capital outflows [30]. This correlation between terrorism and capital flight has been meticulously explored within African nations, revealing a particularly pronounced detrimental effect on industrialization, notably heightened in developing countries [31][32][33]. Similarly, in the context of Asian countries, instances of terrorist attacks have been established as contributing to an escalation in capital flight; however, the amplification of this impact can be mitigated through strategic military expenditures [34,35].…”
Section: Effect Of Terrorism On Capital Flightmentioning
confidence: 99%
“…The works of [32,40,[51][52][53][54][55] have substantially contributed to the literature on corruption. It is important to note that earlier literature frequently defined corruption as the "misuse of public office for private ends or personal gain" [56][57][58].…”
Section: Effect Of Corruption On Capital Flightmentioning
confidence: 99%
“…There is no clarity as to the effect of corruption on economic growth. Some authors consider corruption as an escape route in countries with legal and institutional rigidities ( Méon and Weill, 2010 ), offering lower prices and flexible environmental laws ( Yapatake-Kosole and Ngaba, 2020 ; Li and Rengifo, 2018 ), while others perceive it as an inhibitor of economic growth by discouraging investments ( Nguyen et al., 2014 ) and reducing productivity ( Zakharov, 2019 ). An intermediate position suggests it has a differentiated effect according to the levels of both corruption and growth ( Ahmad et al., 2012 ; Lucic, 2016 ).…”
Section: Introductionmentioning
confidence: 99%